2008
DOI: 10.1200/jco.2007.12.9437
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Quantitative Estrogen and Progesterone Receptor Expression and Human Epidermal Growth Factor Receptor 2 (HER-2) Status With Recurrence in the Arimidex, Tamoxifen, Alone or in Combination Trial

Abstract: Quantitative expression of ER and PgR and HER-2 status did not identify patients with differential relative benefit from anastrozole over tamoxifen: TTR was longer for anastrozole than for tamoxifen in all molecular subgroups. Low ER or PgR or high HER-2 expression are associated with a high risk of recurrence with either anastrozole or tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
277
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(293 citation statements)
references
References 17 publications
12
277
0
4
Order By: Relevance
“…Most studies analyzing predictive or prognostic factors in ER-positive breast cancer have been performed in postmenopausal women, mainly using patients and samples in adjuvant aromatase inhibitor trials [3,4,23]. In premenopausal women, however, even the clinical role of PgR has been little analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies analyzing predictive or prognostic factors in ER-positive breast cancer have been performed in postmenopausal women, mainly using patients and samples in adjuvant aromatase inhibitor trials [3,4,23]. In premenopausal women, however, even the clinical role of PgR has been little analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor (ER) is essential for estrogen-dependent growth, and its level of expression is considered a crucial determinant of response to endocrine therapy and prognosis in ER-positive breast cancer [1][2][3][4]. On the other hand, the clinical role of progesterone receptor (PgR) in ER-positive breast cancer remains controversial, although testing of PgR by immunohistochemistry (IHC) has become routine [5].…”
Section: Introductionmentioning
confidence: 99%
“…6 In two randomized controlled trials of tamoxifen therapy versus no treatment supported the use of tamoxifen as adjuvant therapy. 7 As it has been demonstrated that time to recurrence varies inversely with hormone receptor expression, 8 each patients' likelihood of benefiting from hormonal therapy depends significantly on the degree of ER and PR expression. [9][10][11][12][13][14][15] As tamoxifen has been associated with increased incidence of thromboembolic events and endometrial cancer, it is necessary to evaluate risk versus benefit for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen. 147 Adding trastuzumab 148 or lapatinib 149 in concert improves response to aromatase inhibitors. The finding that mTOR inhibition may reverse resistance to endocrine agents in breast cancer MCF-7 cells 150,151 is consistent with clinical findings; recently, two studies reported addition of the mTOR inhibitor everolimus to endocrine therapy with the aromatase inhibitor exemestane 152 or the anti-oestrogen tamoxifen, 153 to significantly improve response to therapy in cancers nonamplified for HER-2.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%